Mediamorphosis Sebagai Strategi Pertahanan Eksistensi Radio Prambors 102,2 FM Jakarta - Liza Dwi Ratna Dewi; Faiz Fachreza (Fakultas Komunikasi & Desain Kreatif - Universitas Budi Luhur, 2023)
Environmental changes, especially the development of Communication Information Technology (ICT) required change. The process of changing media is known as mediamorphosis. This study determines the formulation of the problem: how is mediamorphosis carried out by Prambors 102.2 FM Radio (Prambors) as a strategy to maintain existence. This study uses the concept of Fidler's mediamorphosis and Castells’s network society. This study applies a qualitative descriptive method. Research subject is Prambors Management. Risearch object is Prambors metamorphosis. Primary data collection by interviewing resource persons: Agatha Theodora, Mayada Sugkar, Filnest Fandary; Observations on the Prambors multiplatform related to Kuis “Kabur Libur” and field observations at “Mendadak Sepedahan” event. Secondary data is collected via the internet from various sites. The research was conducted in June 2021 – April 2022. The analysis divides into 3 parts, namely: work method, media form and media content. In the past, the work method of program design were carried out by brainstorming creative teams, currently it is carried out by brainstorming or listener research which is packaged in various forms of quizzes. The data from this research is then processed by the creative team in a work program called story art. Media form that were originally on air and off air, now exist in multiplatforms that are popular with audiences by not leaving on air and off air. This form will continue to change following the desired form of media audiences. Content that used to contain songs, broadcasters and guest stars, now audiences are part of the content.